Rootstock influence on the characteristics of Persian lime fruits - García-Sandoval, José Ángel; Nava-Padilla, Raymundo Javier; Casasola-Elizondo, César Antonio (Revista Mexicana de Ciencias Agrícolas, 2026)
The use of rootstocks in citrus has been shown to improve agronomic and physicochemical characteristics of the fruit. In Mexico, the ‘Agrio’ orange tree (Citrus aurantium L.) remains the most widely used rootstock despite its phytosanitary limitations. In Quintana Roo, the production and the area planted with citrus increased by 6.3% and 12.1%, respectively, in the last decade. In contrast, the average annual yield decreased by 5%. This research was conducted in 2024 at the Chetumal Experimental Field of the National Institute of Forestry, Agricultural and Livestock Research, with the aim of evaluating the effect of six rootstocks on the physicochemical characteristics of the Persian lime (Citrus latifolia T.) fruit. The weight and equatorial and longitudinal diameters of the fruit, peel color, number of carpels, juice volume, total soluble solids and pH of the juice of Persian lime grafted onto six rootstocks were recorded. To determine the color and total soluble solids, the methodology proposed by the CIE and AOAC was used. The statistical analysis consisted of an analysis of variance (Anova) using a univariate general linear model, under a completely randomized experimental design and Tukey’s test for mean comparison (p≤ 0.05). The results indicate that the ‘Macrophylla’ and ‘Volkameriano’ rootstocks have a higher weight and equatorial diameter of the fruit; in contrast, the ‘Troyer’, ‘Carrizo’, and ‘C-35’ rootstocks are distinguished by inducing a higher content of total soluble solids and higher pH values in the juice.